Two-section branch-line hybrid couplers based broadband transmit/receive switch - Ashraf Abuelhaija; Gameel Saleh (Institute of Advanced Engineering and Science, 2023)
This article introduces a broadband microstripline-based transmit/receive switch for 7-Tesla magnetic resonance imaging. The designed switch aims to handle a signal of multiple frequencies to/from a multi-tuned radio-frequency coil that resonates at frequencies corresponding to the speed of precession of a wide range of atomic X-nuclei, at the same time and without tuning. These include 1H, 23Na, 13C, 31P, 19F, and 7Li used in magnetic resonance spectroscopy as a measure to the existence of many diseases. The fundamental and third harmonic center frequencies of the switch are adjusted to resonate at two broadbands covering a wide range of atomic X-nuclei. Two section branch-line hybrid couplers with phase inverters are designed to build the broadband switch. The designed switch used the minimum trace widths of transmission lines that reveal a compact size without increasing the heat and then the loss beyond specific values. The couplers and the switch S-parameters exhibited good return loss (<-10 dB), high isolation (<-40 dB), less insertion loss (<1 dB) and two clear wide bands covering many atomic X-nuclei used in diagnosis, at the same time and without the need for any tuning circuit during operation.